Case Report: Metastatic Signet-Ring-Cell Carcinoma of the Bladder From Breast Invasive Lobular Carcinoma Detected by Computed Tomography - Jin, Xiaoxiang; Tang, Haibin; Chen, Hualin; Chen, Gang (Frontiers in Oncology, 2022)
Secondary bladder tumors are relatively rare among all bladder tumors, while bladder metastases from breast cancer have been rarely reported. Furthermore, signet-ring differentiation may appear in the metastases from a breast invasive lobular carcinoma regardless of whether the primary breast tumor had signet-ring cells, which may cause diagnostic uncertainty. We report a case of a 55-year-old female patient with diffuse bladder thickening as the chief complaint and no specific clinical manifestations. While the cystoscopy showed multiple scattered red protuberances, the biopsy suggested signet-ring-cell carcinoma. The gastroscopy results suggested poorly differentiated adenocarcinoma with signet-ring cells. Considering the patient's history of invasive lobular carcinoma of the breast, chronic myeloid leukemia, and metastatic endometrial carcinoma from the breast, we performed an immunohistochemical analysis and the results indicated that signet-ring-cell carcinomas of the stomach and bladder originated from the invasive lobular carcinoma of the breast. We performed positron emission tomography/computed tomography and the results showed that there were multiple bone metastases already present. This was the first English case report of invasive lobular carcinoma of the breast metastasizing to the uterus, stomach, bladder, and bones with multiple signet-ring-cell variations. This study shares our reasons for misdiagnosing and opinions on diagnosing and treating for this kind of cases.